The brazilian state and the evaluation educational policies - Melo, Eliane Pimentel Camillo Barra Nova de; Lima, Paulo Gomes [UNESP] (Univ Fed Sao Carlos, 2016)
This article aims to historically analyze the trajectory of the evaluation system of the Basic Education on the 1980s until the ANA's (National Assessment of Alphabetization) implantation. It is verified that in Brazil there were three generations of evaluations; however, education suffers from the same problems of countries that have not invested in assessments. It is evident the external influence in the evaluation system through agreements between Brazilian and international institutions. It is found that there has been major investment in the evaluation system, but little or nothing changes in Brazilian education. The most direct result of this evaluation system was the accountability policy of education professionals for the poor performance of students.
Keywords: Evaluation system; Education; Accountability policy